GRATIFIKASI POLITIK DALAM PEMILIHAN KEUCHIK DI GAMPONG BUNTHA KECAMATAN KRUENG SABEE KABUPATEN ACEH JAYA - Rubami Rubami; Afrizal Tjoetra; Nurkhalis Nurkhlais (Jurnal Society : Pengamat Perubahan Sosial, 2021)
This research was conducted because some of the people of Gampong Buntha still carried out political gratification in the process of selecting village officials. The purpose of this study was to determine the factors of political gratification in the Keuchik election. The theory used is the theory of social exchange. The research method used qualitative methods based on purposive sampling and data collection techniques through interviews and documentation. The results found that the factor of political gratification in society was due to 3 (three) things, namely; want to get a job, get a position back, the people fulfill their daily needs. The efforts made to prevent political gratification in the community in Buntha Village consist of 3 (three) parts, namely; give advance warning and understanding, good supervision and possible re-election.